2017
DOI: 10.1177/1359104517698009
|View full text |Cite
|
Sign up to set email alerts
|

Mother–child interactions in young children with excessive physical aggression and in typically developing young children

Abstract: These data show that children with excessive aggressive behavior develop disrupted mother-infant interactions from a very young age. Several negative interactive features and correlations between child behavior and maternal behavior were found in clinical samples. The effects of these features add up and probably strengthen each other, thus leading to interactive difficulties from a very young age. More attention should be paid to early parent-child interactions in case of child behavioral problems. The recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
4
2
Order By: Relevance
“…The literature search outlined above yielded 39 articles that met the preregistered inclusion criteria (see Table 1 for an overview). Contrary to our assumption in the preregistration, however, only a few of the articles directly investigated the quality of parent-child play in association with child behavioral adjustment (Gardner, 1994 ; Landy and Menna, 2001 ; Gardner et al, 2003 ; Ahnert et al, 2017 ; Urbain-Gauthier and Wendland, 2017 ) and no studies were found directly investigating parental playfulness. Instead, the majority of studies used parent-child play as a context for observing general parental and child interaction variables that were then examined for a connection with behavioral adjustment.…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The literature search outlined above yielded 39 articles that met the preregistered inclusion criteria (see Table 1 for an overview). Contrary to our assumption in the preregistration, however, only a few of the articles directly investigated the quality of parent-child play in association with child behavioral adjustment (Gardner, 1994 ; Landy and Menna, 2001 ; Gardner et al, 2003 ; Ahnert et al, 2017 ; Urbain-Gauthier and Wendland, 2017 ) and no studies were found directly investigating parental playfulness. Instead, the majority of studies used parent-child play as a context for observing general parental and child interaction variables that were then examined for a connection with behavioral adjustment.…”
Section: Resultscontrasting
confidence: 56%
“…With respect to maternal responsiveness during play, a longitudinal study with a large sample of 424 dyads showed that children whose mothers were more sensitive and receptive in a play interaction were more likely to be assigned to a prosocial group than to an aggressive group (Jambon et al, 2019 ). Studies by Landy and Menna ( 2001 ) and Urbain-Gauthier and Wendland ( 2017 ) show similar results in relation to samples with aggressive children, revealing reduced maternal responsiveness and sensitivity in observed mother-child interactions compared to control groups with typically developing children. In addition, an observational study by Ambrose and Menna ( 2013 ) investigating interactional synchrony, supports these results.…”
Section: Narrative Synthesismentioning
confidence: 55%
See 2 more Smart Citations
“… 1 - 3 Positive mother–child interaction is one of the factors associated with positive outcomes in many areas of child development. 4 - 6 The mother's behavior and competency in fulfilling the baby's needs affect mother–child interactions. Positive interactions of babies with their mothers make them more curious about the environment and allow them to be more open to discovering the surrounding objects.…”
Section: Introductionmentioning
confidence: 99%